Safe Harbors for Quantity Discounts and Bundling - Dennis W. Carlton; Michael Waldman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
The courts and analysts continue to struggle to articulate safe harbors for a wide variety of common business pricing practices in which either a single product is sold at a discount if purchased in bulk or in which multiple products are bundled together at prices different from the ones that would emerge if the products were purchased separately. The phenomenon of tying in which the sale of one product is conditioned on the purchase of another is closely related to bundling. Its analysis relies on the same economics as that used to analyze bundling (see, e.g., Carlton and Waldman (2008)), though the law seems to make a distinction between the two. The need for safe harbors for common business pricing practices arises from the recognition that these practices often are motivated by efficiency and that a broad antitrust attack on them could cause more harm than good. In this essay, we analyze and propose safe harbors for quantity discounts and bundled products. In analyzing the latter case, we discuss the deficiencies of the particular safe harbor proposed in the report of the Antitrust Modernization Commission (2007) (AMC) of which Carlton was a member.
Keywords: L41; L42; K21; 330; Tying; Bundling; Safe Harbor; Antitrust